Cherubism - A case report with long term follow up - Lakshmi V Chavali; R M Rao Bhimalingam; P V Sudhakar (Wolters Kluwer Medknow Publications, 2011)
Cherubism is a rare non-neoplastic disease of the bone characterized by bilateral painless enlargement of the jaws giving a cherubic appearance to the patient. It is an autosomal dominant disorder but may occur sporadically. In this paper, we have tried to explain about the clinical, radiological and histopathologic features of cherubism by presenting a case study. A case study of a 7 year old male patient, who first presented with mandibular bilateral swellings to our department in 1998, has been presented. In-depth clinical, radiological and histopathologic examination was done. An extensive long-term follow-up till 11 years was maintained. When presented for the first time, radiological investigation showed characteristic multilocular lytic lesions of the mandible bilaterally. Histopathological examination of the biopsy specimen showed proliferating fibrous connective tissue interspersed by multinucleated giant cells. It was diagnosed as a case nonfamilial cherubism. Follow-up after 5 years showed involvement of the maxilla as well, which was then corrected by surgical methods. Upon follow up 11 years after the first presentation, it was seen that the lesion was regressing by itself and there was improvement in facial contour. The natural course of Cherubism through its progression, stabilization and involution of the disease after puberty, has been highlighted in this case. More, in-depth studies to understand the nature and the pathogenesis of this condition better are required.